2024
DOI: 10.1002/smll.202310926
|View full text |Cite
|
Sign up to set email alerts
|

CeO2‐Based Frustrated Lewis Pairs via Defective Engineering: Formation Theory, Site Characterization, and Small Molecule Activation

Run Jing,
Xuebin Lu,
Jingfei Wang
et al.

Abstract: Activation of small molecules is considered to be a central concern in the theoretical investigation of environment‐ and energy‐related catalytic conversions. Sub‐nanostructured frustrated Lewis pairs (FLPs) have been an emerging research hotspot in recent years due to their advantages in small molecule activation. Although the progress of catalytic applications of FLPs is increasingly reported, the fundamental theories related to the structural formation, site regulation, and catalytic mechanism of FLPs have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…In contrast, Nb 2 O 5 (with stronger acidic sites than CeO 2 ) did not catalyze the benzilic-acid rearrangement step. These results and the fact that metal oxides with Lewis acid and base sites reported to act as CLPs did not induce the rearrangement step show that the exceptional catalytic performance of CeO 2 is possibly due to the concerted activation of diaryl 1,2-diketones by the unique Lewis acid–base pairs composed of lattice oxygen as the Lewis base and Ce 3+ and/or Ce 4+ as the Lewis acid, such as solid frustrated Lewis pairs (FLPs). …”
Section: Resultsmentioning
confidence: 91%
“…In contrast, Nb 2 O 5 (with stronger acidic sites than CeO 2 ) did not catalyze the benzilic-acid rearrangement step. These results and the fact that metal oxides with Lewis acid and base sites reported to act as CLPs did not induce the rearrangement step show that the exceptional catalytic performance of CeO 2 is possibly due to the concerted activation of diaryl 1,2-diketones by the unique Lewis acid–base pairs composed of lattice oxygen as the Lewis base and Ce 3+ and/or Ce 4+ as the Lewis acid, such as solid frustrated Lewis pairs (FLPs). …”
Section: Resultsmentioning
confidence: 91%
“…Additionally, studies have shown oxygen vacancies serve as Lewis acid centers, enabling CO 2 hydrogenation reactions [23]. Lewis acid sites are often associated with oxygen vacancies and are commonly found in metal oxides, such as In 2 O 3 and CeO 2 [24]. Lewis acid sites are coordinatively unsaturated metal cations, and adjacent unobstructed lattice oxygen serves as a Lewis basic site.…”
Section: Introductionmentioning
confidence: 99%